Comparative Physiological and Transcriptomic Analyses Reveal Altered Fe-Deficiency Responses in Tomato Epimutant Colorless Non-ripening - Chen, Wei Wei; Zhu, Hui Hui; Wang, Jia Yi; Han, Guang Hao; Huang, Ru Nan; Hong, Yi Guo; Yang, Jian Li (Frontiers in Plant Science, 2022)
The mechanisms associated with regulation of iron (Fe) homeostasis have been extensively examined, however, epigenetic regulation of these processes remains largely unknown. Here, we report that a naturally occurring epigenetic mutant, Colorless non-ripening (Cnr), displayed increased Fe-deficiency responses compared to its wild-type Ailsa Craig (AC). RNA sequencing revealed that a total of 947 and 1432 genes were up-regulated by Fe deficiency in AC and Cnr roots, respectively, while 923 and 1432 genes were, respectively, down-regulated. Gene ontology (GO) analysis of differentially expressed genes (DEGs) showed that genes encoding enzymes, transporters, and transcription factors were preferentially affected by Fe deficiency. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis revealed differential metabolic responses to Fe deficiency between AC and Cnr. Based on comparative transcriptomic analyses, 24 genes were identified as potential targets of Cnr epimutation, and many of them were found to be implicated in Fe homeostasis. By developing CRISPR/Cas9 genome editing SlSPL-CNR knockout (KO) lines, we found that some Cnr-mediated Fe-deficiency responsive genes showed similar expression pattern between SlSPL-CNR KO plants and Cnr epimutant. Moreover, both two KO lines displayed Fe-deficiency-induced chlorosis more severe than AC plants. Additionally, Cnr mutant displayed hypermethylation in the 286-bp epi-mutated region on the SlSPL-CNR promoter, which contributes to repressed expression of SlSPL-CNR when compared with AC plants. However, Fe deficiency induced no change in DNA methylation both at the 286-bp epi-allele region and the entire region of SlSPL-CNR gene. Taken together, using RNA-sequencing and genetic approaches, we identified Fe-deficiency responsive genes in tomato roots, and demonstrated that SlSPL-CNR is a novel regulator of Fe-deficiency responses in tomato, thereby, pave the way for further functional characterization and regulatory network dissection.